2011
DOI: 10.1007/s10886-011-9947-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydrocarbons on Harvester Ant (Pogonomyrmex barbatus) Middens Guide Foragers to the Nest

Abstract: Colony-specific cuticular hydrocarbons are used by social insects in nestmate recognition. Here, we showed that hydrocarbons found on the mound of Pogonomyrmex barbatus nests facilitate the return of foragers to the nest. Colony-specific hydrocarbons, which ants use to distinguish nestmates from non-nestmates, are found on the midden pebbles placed on the nest mound. Midden hydrocarbons occur in a concentration gradient, growing stronger near the nest entrance, which is in the center of a 1-2 m diameter nest m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 36 publications
1
14
0
1
Order By: Relevance
“…First, foragers require a rapid rate of return of patrollers [16], about 1 per 10 sec, to leave the nest for the first time in the morning, indicating there is a short window during which foragers react to encounters with returning ants. Second, foraging activity responds very quickly, within minutes, in response to a change in forager return rate [23][24]; [35][36].…”
Section: Discussionmentioning
confidence: 99%
“…First, foragers require a rapid rate of return of patrollers [16], about 1 per 10 sec, to leave the nest for the first time in the morning, indicating there is a short window during which foragers react to encounters with returning ants. Second, foraging activity responds very quickly, within minutes, in response to a change in forager return rate [23][24]; [35][36].…”
Section: Discussionmentioning
confidence: 99%
“…In some cases, SPME fibers can be saturated by a disproportionate concentration of one or more compounds from a specific body segment (Ferreira-Caliman, personal observation), but we did not observe such saturation with the Chromosorb®. Furthermore, it may be possible to mix Chromosorb® with nest materials in experiments on orientation of ants (Sturgis et al, 2011) or in analyses of bee comb waxes (stingless bees: Pianaro et al, 2007;honeybees: D'Ettorre et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Cuticular hydrocarbons [i.e., molecules that are usually responsible for nestmate recognition in hymenopterans (9)] were found to occur in a concentration gradient surrounding the nest entrance. An experiment in which the natural gradient was changed resulted in decreased homing speeds, suggesting that homing ants use this gradient (102). In consideration of both results, it seems reasonable that ants generally use whatever olfactory cue helps pinpoint the nest.…”
Section: Olfactory Cuesmentioning
confidence: 91%
“…Indeed, displaced homing ants exposed to an artificial CO 2 plume will follow it as though it originated from a real nest (14). Another study found that P. barbatus pinpoints the nest by following olfactory cues (102). Cuticular hydrocarbons [i.e., molecules that are usually responsible for nestmate recognition in hymenopterans (9)] were found to occur in a concentration gradient surrounding the nest entrance.…”
Section: Olfactory Cuesmentioning
confidence: 99%